Cultivating Students’ Character through Security Governance, Discipline, and Habituation in Pondok Modern Darussalam Gontor Putri 3 - R. Nabila Zaty Shakila; Rahmania Eliza; Ulfi Azizia Maulana; Syarifah Syarifah; Nurus Salis Alamin (Journal of Indonesian Islamic Studies, 2026)
Character education has become a strategic priority in contemporary education, particularly within Islamic boarding schools (pesantren), which provide a holistic environment for students' moral, social, and spiritual development. This study aims to examine how students’ character is cultivated through the integration of security governance, institutional discipline, and habituation at Pondok Modern Darussalam Gontor Putri 3. Employing a qualitative ethnographic approach, the research was conducted over six months involving participant observation, semi-structured interviews with institutional leaders, dormitory supervisors, OPPM Security Division members, student leaders, and students, as well as document analysis. The data were analyzed using Reflexive Thematic Analysis integrated with ethnographic interpretation. The findings reveal that security governance functions not merely as a disciplinary mechanism but as an educational governance system that fosters responsibility, accountability, and leadership through continuous supervision and peer-led organizational practices. Institutional discipline provides structured routines that encourage self-regulation, while habituation internalizes moral values through repetitive educational and religious activities. The interaction of these three dimensions produces a sustainable process of value internalization that shapes students' responsibility, integrity, independence, leadership, and self-control. This study proposes an integrated governance-based model of character cultivation, demonstrating that security governance serves as the connecting mechanism linking institutional discipline and habituation within the twenty-four-hour educational ecosystem of the pesantren. The findings contribute theoretically to the discourse on governance-based character education and offer practical implications for strengthening student character through organizational culture and experiential learning in Islamic educational institutions.